Botswana : Report on the Observance of Standards and Codes-Data Module-Update. (IMF Staff Country Reports; Country Report ;, 2004)
The high priority recommendations from the data report on the observance of standards and codes mission covered both general and sector-specific issues relating to the national accounts, consumer and producer price indices, government finance statistics, monetary statistics, and balance-of-payments statistics. Progress has been made in implementing the recommendation on data sharing and coordination among agencies. A high-level statistics producers committee has been established. Progress on quarterly national accounts data has been slow because of poor response rates to the surveys.